Metformin Reduces the Risk of Total Hip Arthroplasty in Elderly Patients with Hip Osteoarthritis and Type 2 Diabetes Mellitus - Li F (Diabetes, Metabolic Syndrome and Obesity, 2023)
Fuchun Li Fourth Department of Orthopedics, The First Affiliated Hospital of Harbin Medical University, Harbin, 150001, People’s Republic of ChinaCorrespondence: Fuchun Li, Fourth Department of Orthopedics, The First Affiliated Hospital of Harbin Medical University, 23 Youzheng Str, Nangang District, Harbin, 150001, People’s Republic of China, Email lifuchunhb@163.comPurpose: To assess if metformin could reduce the risk of total hip arthroplasty (THA) in elderly patients with hip osteoarthritis and type 2 diabetes (T2DM).Patients and Methods: It is a retrospective study among elderly patients (≥ 65 years) with hip osteoarthritis and T2DM. All included patients were divided into metformin group and non-metformin group, then propensity-score match (PSM) was performed to control potential confounding factors. The primary endpoint was the incidence of the first THA during the study period. Multivariate Cox regression analysis was employed to evaluate the association of metformin with the risk of THA.Results: A matched cohort of 716 patients were finally included, with 308 metformin users and 308 metformin non-users. During a maximum follow-up of 10 years, the incidence of THA in metformin users was significantly lower than that in non-users (4.9% vs 25.0%, P< 0.01). Multivariate Cox regression analysis indicated that metformin users were significantly associated with a lower risk of THA compared with non-users (HR = 0.17, 95% CI: 0.10– 0.30; P< 0.01). In addition, further analyses indicated that participants with long-term metformin use (HR = 0.10, 95% CI: 0.02– 0.46; P< 0.01) or high metformin dosage (HR = 0.15, 95% CI: 0.04– 0.57; P< 0.01) had a lower risk of THA.Conclusion: Metformin use could reduce the risk of THA in patients with hip osteoarthritis and T2DM, and the effect is accumulative and dose dependent.Keywords: hip osteoarthritis, total hip arthroplasty, type 2 diabetes, metformin